Faults in Cloud Environment - Lobato, Renata Spolon [UNESP]; Da Silva, Fabio Amorim [UNESP]; Spolon, Roberta [UNESP]; Manacero, Aleardo [UNESP]; Tamashiro, Camila Baleiro Okado; Cavenaghi, Marcos Antonio (My University, 2021)
Cloud computing is an area in great expansion in the recently years and have begin to be indispensable for greatest majority of world population, even for those who do not work directly on technical areas. One of the greatest challenge in this field encompass the planning of systems in a way to decrease implementation costs while maximizing the efficiency; simulation can be used evaluate alternatives on part of the project. Fault injection is one of the main aspects that can be tackled by simulation. Unhandled faults on the cloud environment can lead to downtime and financial losses. This paper presents the implementation of new faults in the fault injection system for the cloud simulator iSPD (iconic Simulator for Parallel and Distributed Systems), aiming at enhancing the simulation tool, and improving users experience on it.
Falhas em Ambiente de Nuvem
Keywords: cloud computing; faults; simulation